ROTACIÓN y AUSENTISMO LAbORAL EN EL pARQUE INDUSTRIAL DE vILLA EL SALvADOR - Tito Huamaní, Pedro Leonardo (2013)
Absenteeism and labor turnover are indicators of management that allows us to measure the level of satisfaction of the worker in his workplace. Absenteeism is defined as the permanent withdrawal of the staff of the organization where you work. It is also seen as an abandonment or absence of workers and the duties to be fulfilled. Also not only considered as the absence in the workplace but also as non-performing by the employee of the consideration of their services in exchange for wages, ie not perform productive work for the company where he works. The OIT defines as “nonattendance at work by an employee who was thought he would attend, excluding holiday periods and strikes, and absenteeism of medical cause, as the period of sick leave attributable to an inability the individual, except for the derivative of normal pregnancy or imprisonment”. On the other hand means that labor turnover as staff fluctuation between an organization and its environment, this means, exchange of personnel between the organization and the environment is defined by the volume of people entering and leaving the organization. As a management tool, this variable measures the stability of employment, which is defined as the number of hits and separations (inflows and outflows of staff) over a period of time. Both phenomena were investigated in the business empire Mype Industrial Park of Villa El Salvador (PIVES), proving our assumptions postulating that both absenteeism and turnover affect labor productivity, and significantly exceed the average rate of the productive sector in our midst.